Penerapan Algoritma K-Means Dalam Pengelompokan Rasio Angka Partisipasi Kasar di Tingkat Pendidikan Perguruan Tinggi Menurut Provinsi - Simanjorang, Fernandi; Winanjaya, Riki; Rizki, Fitri (TIN: Terapan Informatika Nusantara, 2021)
The Ratio of Gross Participation Rate of Education is a very important role holder in the development of the nation and state, because that's where the intelligence and ability and even the character of the nation in the future is determined by education at this time. This study discusses the grouping of the number of ratios of gross participation rates by province in Indonesia. The method used is datamining with the K-means clustering algorithm. Using this method the data obtained can be grouped into 3 clusters. This study uses secondary data that is data obtained through intermediary media recorded on the website of the central statistics agency with the url address: http://www.bps.go.id. The results obtained in this study are the grouping of the ratio of gross participation rates of education grouped into 3 clusters, namely the highest cluster and the lowest cluster. In this study is expected to provide input to the relevant government, in order to pay more attention to the provinces that are included in the lowest cluster to overcome the level of quality of universities